EMPERICAL ANALYSIS OF MERGER IN BANKING SECTOR: A CASE STUDY OF MERGER OF BANK OF RAJASTHAN WITH ICICI BANK (International Journal of Food and Nutritional Sciences, 2022)
The primary objective of an organization towards M &A's is to create a niche of core competencies and improve transform the organizational culture to a better and improved form. It helps in design and develops systems in accordance to the changing face of business across all industrial sectors. An organization aims in Mergers and acquisitions are committed to extend the relationship with clients beyond the professional horizons to provide them high level of satisfaction and assurance. Merger deals are grouped into 3 categories viz, Voluntary Merger, Compulsory Merger and Universal Banking Model which is based on the motives. The ICICI Bank Merger with Bank of Rajasthan is the seventh voluntary merger and the latest in India after the merger of HDFC Bank - Centurion Bank of Punjab in the year 2008, compared with other voluntary mergers. This deal also has background of the merger including various regulatory interventions of authorities like the Reserve Bank of India (RBI), Securities and Exchange Board of India (SEBI) and Foreign Investment Promotion Board (FIPB). Because of poor corporate governance of the target bank and cancellation of Extra Ordinary General Meeting (EGM) by the Calcutta District Civil Court this deal also got lots of attention. In this case, an attempt has been made to analyze the probable impact of strategic tools and features of the banks on pre and post merger performance.